Arbuscular mycorrhizal fungi alleviate elevated temperature and nitrogen deposition- induced warming potential by reducing soil N2O emissions in a temperate meadow - Nan Cui (Elsevier, 2021)
Nitrous oxide (N2O) is one of the most important greenhouse gases and has the potential to aggravate global warming. Arbuscular mycorrhizal (AM) fungi form mutualistic associations with most terrestrial plants, which can help plant nitrogen (N) uptake and have also been shown to reduce soil N2O emissions. However, the development and species community composition of AM fungi are influenced by warming and N deposition. To date, the mechanism by which warming, N deposition, and AM fungi interactively affect soil N2O emissions in the field is still poorly understood. We implemented elevated temperature and N addition treatments in a 5-year experiment in a semiarid temperate meadow to examine the impact of AM fungi on soil N2O fluxes under the treatment conditions. Both elevated temperature and N deposition and the combination of the two significantly increased soil N2O emissions. AM fungi reduced soil N2O emissions under elevated temperature and N deposition. The decrease in soil N2O emissions by AM fungi was lower under elevated temperature than N deposition. Under elevated temperature, the AM fungal decrease in soil N2O emissions was mainly determined by the abundance of the functional genes ammonia-oxidizing bacteria (AOB) and nosZ, while the AM fungal reduction in soil N2O emissions was mainly affected by soil microbial biomass carbon under N deposition. These results indicate that although AM fungi could reduce soil N2O emissions the pathway by which AM fungi regulate soil N2O emissions might vary under different global change contexts with elevated temperature or nitrogen deposition. Our results highlight the negative effect of AM fungi on soil N2O emissions under elevated temperature and N deposition and show that the influence of AM fungi on N2O emissions might be simultaneously determined by warming, N deposition and ecosystem types. The results of the study help to evaluate the potential role of AM fungi in reducing N2O emissions from grassland ecosystems in the context of future global change and provide a theoretical basis for sustainable grassland management.